What doesn't kill you makes you stronger? Evidence from vampire attacks on decentralized exchange and non‐fungible token marketplace - Zhao, Xi; Jian, Li; Wan, Xiang; Zang, Xinyu; Cheng, Hsing Kenneth (Journal of Operations Management, 2024)
We examine the impact of vampire attack, a unique platform entry strategy in the blockchain ecosystem, on the operational performance of the incumbent platform. During the vampire attack period, the entrant (attacker) clones the incumbent platform and offers tokenized incentives to entice users away from the incumbent. Prior studies offer little insight into the impact of vampire attack strategy because of its uniqueness in platform cloning, tokenized incentives, and targeted attacks. We implement a quasi‐experimental design by leveraging the first and most famous vampire attack launched by SushiSwap (the attacker) against Uniswap (the incumbent). We examine both the deposit‐side and exchange‐side impacts of the vampire attack on the operational performance of the liquidity pools on Uniswap. Surprisingly, we find that the vampire attack has no significant effect on the liquidity provision on the deposit side. Even more surprisingly, the vampire attack significantly increases the incumbent's trading volume on the exchange side. We further uncover the underlying mechanisms contributing to these intriguing results. We also demonstrate the efficacy of the novel tokenized incentives strategy. We show the generalizability of our findings by examining an alternative vampire attack event in the context of non‐fungible token marketplaces. Our study offers significant contributions to the literature on the implications of blockchain on platform operations and platform competition in operations management.